2006
DOI: 10.1063/1.2245192
|View full text |Cite
|
Sign up to set email alerts
|

As-doped p-type ZnO films by sputtering and thermal diffusion process

Abstract: As-doped p-type ZnO films were grown on GaAs by sputtering and thermal diffusion process. Hall effect measurements showed that the as-grown films were of n-type conductivity and they were converted to p-type behavior after thermal annealing. Moreover, the hole concentration of As-doped p-type ZnO was very impressible to the oxygen ambient applied during the annealing process. In addition, the bonding state of As in the films was investigated by x-ray photoelectron spectroscopy. This study not only demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 23 publications
0
33
1
Order By: Relevance
“…A broad peak corresponding to 42.2-42.7 eV was observed in the as-grown film. The peak appeared at this binding energy region may be attributed to amorphous elemental As [12]. XPS spectra of As 3d core level at 45.6 eV was detected for the annealed films.…”
Section: Resultsmentioning
confidence: 97%
“…A broad peak corresponding to 42.2-42.7 eV was observed in the as-grown film. The peak appeared at this binding energy region may be attributed to amorphous elemental As [12]. XPS spectra of As 3d core level at 45.6 eV was detected for the annealed films.…”
Section: Resultsmentioning
confidence: 97%
“…Arsenic is more volatile than gallium and thus it starts to diffuse at a lower annealing temperature. This method was successfully used by Cheng et al [13] and Wang et al [15] to achieve p-type conductivity in ZnO with a hole concentration of around 10 20 cm À3 . From the literature, it is observed that such a large carrier concentration was not achieved by any other means.…”
Section: Introductionmentioning
confidence: 93%
“…Arsenic can also be doped into ZnO, by using GaAs as the substrate as well as the source of arsenic. Directional thermal treatment of the samples (ZnO/GaAs) facilitates diffusion of arsenic from GaAs substrate into ZnO films [13,15]. Arsenic is more volatile than gallium and thus it starts to diffuse at a lower annealing temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, group V elements, such as N, P, As, and Sb were utilized as p-type dopants to form rather stable ptype ZnO films [1][2][3][4]. In particular, rapid thermal annealing and the post annealing converted semi-insulating ZnO:P films into stable and reproducible p-type ZnO:P ones [5,6].…”
mentioning
confidence: 99%